NEW AND CRITICAL MALAYSIAN PLANTS-I - A. J. G. H. KOSTERMANS (Reinwardtia, 1953)
Ab omnibus speciebus generis legumine permagno,falcitto vel subfalcato et foliolis magnis differt.Tree up to 30 m high, with a clear bole 21 m high and 50 cm indiameter.Buttresses up to 2 m high, extending 1 m from bole, 5—10 cmthick. Bark grey-brown, rather smooth or cracked,occasionally scaling off in irregular pieces; dead bark 2—9 mm thick; living bark 5—9 mm,red. Sapwood 5—15cm, yellowish, with agreeable smell; heartwood redbrown.Branches cylindrical, red-brown or grey, lenticellate; branchlets at apex rusty puberulous.Leaves bipinnate, up to 35 cm long, glabrous,glandless; petioles 3—12 cm long, glabrous or microscopically pulverulently puberulous; rachillae 2 or 4, up to 25 cm long, lower ones shorter; leaflets opposite or the proximal ones subopposite, coriaceous or chartaceous, glabrous, 4—5-jugate (apical leaves 3-jugate), elliptic, (4—)6—12 cm long, (1.5—)3—8cm wide; proximal ones as a rule smaller than distal ones; top acuminate or caudate-acuminate with blunt tip; base rounded or subacute; both surfaces glossy (lower one brown when dried) ; upper surface reticulate or rather smooth; lower surface with prominent midrib and 4—6 pairs of inarching, prominent, lateral nerves; veins prominulous,laxly reticulate; petiolules 3—5 mm long, usually stout, deeply channelled above (sometimes not channelled in swollen petiolules). Inflorescence raceme-like, up to 10 cm long, with stout main rachis. Flowers in axils of more or less persistent, ovate, concave, glabrous, 1—2 mm long bracts.Calyx unknown. Corolla-tube unknown; lobes elliptic-lanceolate, concave,glabrous, 3—5 mm long. Anthers 1 mm long. Pod woody, up to 24 cm long and 4.5 cm wide, constricted between seeds, falcate or subfalcate, 2-seeded,dull, ferrugineous (when dried), furrowed, not dehiscent; dorsal suture conspicuous. Seeds brown, ellipsoid, 4 cm long, 2.5 cm wide, hardly com- pressed, top oblique; cotyledons flat-convex, hard.